What Affects Sports Participation and Life Satisfaction Among Urban Residents? The Role of Self-Efficacy and Motivation - Yu, Guo; Song, Yu (Frontiers in Psychology, 2022)
As a result of the global pandemic, new awareness and perceptions of physical and mental health are changing. How to promote people's participation in sports to improve their physical fitness and how to increase their life satisfaction are urgent issues for attention. This study is aimed to discover the mechanisms that influence sports participation and life satisfaction among urban residents, focusing on the role of self-efficacy and motivation. A questionnaire survey on sports participation of Shanghai residents in China found that self-efficacy significantly and positively influenced sports participation; sports participation significantly and positively influenced life satisfaction; and motivation positively influenced sports participation and mediated between self-efficacy and sports participation, but sports participation did not mediate between self-efficacy and life satisfaction. Therefore, it is important to enhance people's self-confidence in sports participation and establish the concept of sports for all people, so as to strengthen people's motivation to participate in sports, and to guide people to exercise actively through national fitness, so that more people can be happy in sports.